2011
DOI: 10.1080/87565641.2010.549979
|View full text |Cite
|
Sign up to set email alerts
|

Components and Developmental Differences of Executive Functioning for School-Aged Children

Abstract: This study examined the developmental differences, components, and underlying factor structure of executive functioning (EF) in school-aged children by utilizing subtests from Test of Everyday Attention for Children and some additional EF tests. The developmental differences identified across age groups between 7 to 14 years for a sample of 185 children support a multistage interpretation of EF development. Structural equation modeling was used to test models with three first-order EF components which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
50
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 37 publications
15
50
0
7
Order By: Relevance
“…The school-age period was targeted for two reasons. First, the three EF components that were the focus of the present study have been confirmed in school-age children (Duan et al, 2010;Rose et al, 2011;Wu et al, 2011). In younger children, there was a possibility of finding a more integrated EF system (e.g., Wiebe, Espy, & Charak, 2008).…”
Section: The Current Studysupporting
confidence: 66%
“…The school-age period was targeted for two reasons. First, the three EF components that were the focus of the present study have been confirmed in school-age children (Duan et al, 2010;Rose et al, 2011;Wu et al, 2011). In younger children, there was a possibility of finding a more integrated EF system (e.g., Wiebe, Espy, & Charak, 2008).…”
Section: The Current Studysupporting
confidence: 66%
“…With regard to the first goal of our study-to test a model of EF comprised of a sequential flow of cognitive processes-the exploratory factor analysis conducted on the neuropsychological measures of the EF battery identified five latent dimensions of neurocognitive functioning that support a unified model of EF in children: Inhibition, Planning, Execution, and Memory of Performance, sustained by Speed of Processing. In fact, our data support a "sequential" EF model, wherein EF could represent consecutive cognitive processes (see, for example, Burgess et al, 2000;Zelazo & Frye, 1998) rather than other neurocognitive models that have proposed a division of EF into distinct and fractionated domains (see, for example, Letho et al, 2003;Wu et al, 2011). More specifically, the present results are consistent with the "ecological" EF model proposed by Burgess et al (2000).…”
Section: Discussionsupporting
confidence: 91%
“…Executive functions have at least three components (inhibition, shifting, and updating; see Miyake et al, 2000;Wu et al, 2011), but on higher levels, other components are also known to exist, such as planning, self regulation, monitoring, and strategy using (Zelazo & Müller, 2002). The inference to be drawn from meta-analyses is that the executive profiles of ADHD have a large heterogeneity (Sergeant, Geurts, & Oosterlaan, 2002;Willcutt, et al, 2005).…”
Section: Executive Functions In Adhdmentioning
confidence: 99%